VelC positively controls sexual development in Aspergillus nidulans. - Hee-Soo Park; Tae-Young Nam; Kap-Hoon Han; Sun Chang Kim; Jae-Hyuk Yu (PLoS ONE)
Fungal development and secondary metabolism is intimately associated via activities of the fungi-specific velvet family proteins including VeA, VosA, VelB and VelC. Among these, VelC has not been characterized in Aspergillus nidulans. In this study, we characterize the role of VelC in asexual and sexual development in A. nidulans. The velC mRNA specifically accumulates during the early phase of sexual development. The deletion of velC leads to increased number of conidia and reduced production of sexual fruiting bodies (cleistothecia). In the velC deletion mutant, mRNA levels of the brlA, abaA, wetA and vosA genes that control sequential activation of asexual sporulation increase. Overexpression of velC causes increased formation of cleistothecia. These results suggest that VelC functions as a positive regulator of sexual development. VelC is one of the five proteins that physically interact with VosA in yeast two-hybrid and GST pull down analyses. The ΔvelC ΔvosA double mutant produced fewer cleistothecia and behaved similar to the ΔvosA mutant, suggesting that VosA is epistatic to VelC in sexual development, and that VelC might mediate control of sex through interacting with VosA at specific life stages for sexual fruiting.